The Effect of Zizyphus jujube on Serum Lipid Profile and Some Anthropometric Measurements - Mostafa, Usama El-Sayed; Labban, Louay (Pakistan Journal of Nutrition, 2013)
Zizyphus jujube (Z. jujube) is a thorny Rhamnaceous plant that is widely distributed in Europe and South-Eastern Asia. It’s used in traditional medicine for its therapeutic properties. The aim of this study was to find out the possible anti-obesity and hypolipidemic activity of different doses (5, 15 and 30 g/day) of Z. jujube powder and to evaluate its effect on liver function. A group of 83 persons (41 men and 42 women) aged 20-57 years (32±13) participated in this study. They were divided into three groups according to their Body Mass Index (BMI). Z. jujube powder was prepared and a specific questionnaire was given to the participants. Blood specimens were collected and several tests were performed to determine lipid profile and serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST). A group of anthropometric measurements were taken as well. This procedure was repeated after three months. The results indicated a significant reduction in Total Cholesterol (TC), Low Density Lipoprotein Cholesterol (LDL-C), BMI, fat percentage and body weight after administration of doses (5, 15 and 30 g/day) of Z. jujube powder in all groups. Triglycerides (TG) were reduced significantly after consumption 30 g/day of Z. jujube powder. A slight increase in High Density Lipoprotein Cholesterol (HDL-C) was observed. Z. jujube impact on weight status was significant after consumption 30 g/day of Z. jujube powder, While, the impact of other doses were not. It can be concluded that different doses of Z. jujube powder possess hypolipidemic and anti-obesity properties and didn’t show any negative impact on liver function as measured by (ALT and AST).